Kesalahan diksi dan struktur kalimat dalam warta jemaat GMIT Kota Kupang: Tinjauan dari perspektif keterbacaan dan pemahaman - Nurhuda, Aris; Malay, Narantoputrayadi M.; Nitbani, Semuel H.; Djokaho, Margaret P. E.; Leda, Anastasia J. M. (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The aim of this study is to explore the contribution of diction and effective sentences to the readability and comprehension of the GMIT Congregational Bulletin in Kota Kupang. The research employs a qualitative descriptive method to provide an in-depth explanation of linguistic phenomena, particularly the use of diction and effective sentence construction. The findings reveal several errors in word choice and sentence structure, such as excessive word use, influence of colloquial language, and improper sentence arrangement, which lead to vague meanings and ineffective message delivery. Accurate word choice—including appropriate conjunctions, precise synonyms, and the avoidance of nonstandard or redundant words—can clarify meaning and aid reader comprehension. Effective sentences, characterized by clarity, precision, and appropriateness, help prevent confusion and enhance the reader’s understanding of the bulletin content. The implications of this study encourage the bulletin’s editorial team to conduct regular training on effective writing for writers and church administrative staff. Furthermore, it is recommended to develop an internal writing guide that includes language usage rules and examples of well-constructed sentences to ensure consistency and language quality in every edition of the GMIT Congregational Bulletin.